No evidence for PAPE-induced jumping performance enhancement following isometric and treadmill warm-ups in team sport athletes - Artur TERBALYAN; Anna ŚCISŁOWSKA-CZARNECKA; Adam MASZCZYK; Robert ROCZNIOK (Baltic Journal of Health and Physical Activity)
Background: This study aimed to determine whether an isometric PAPE‐based warm-up could enhance jumping performance compared to a traditional treadmill jogging warm-up in team sport athletes. The primary focus was on assessing neuromuscular activation and performance indicators such as jump height and force asymmetry. Materials and Methods: Fifty-three athletes from basketball, volleyball, handball, and soccer participated in a controlled, parallel-group experiment. Participants performed either a unilateral isometric warm-up protocol – comprising two sets of four exercises per leg– or a 5‐minute treadmill jogging session, with jump performance assessed via countermovement jump tests on dual force plates. A split-plot ANOVA was employed to analyze key variables including jump height, concentric mean force asymmetry, and the rate of force development. Results: The analysis revealed no significant differences in performance outcomes between the isometric and treadmill warm-up conditions. While a main effect of sex was observed on jump height, neither warm-up modality produced significant improvements in force asymmetry or the rate of force development. Conclusions: Under the tested conditions, the isometric PAPE-based warm-up did not offer a performance advantage over traditional treadmill jogging. Further research is warranted to explore variations in intensity, duration, and protocol design to optimize acute neuromuscular responses.